Preparation, Characterization, Properties And Degradation Behaviour Of Peanut Shell Powder Recycled Polypropylene Composites - Zaaba, Nor Fasihah (2017)
Recycled polypropylene (RPP) was compounded with peanut shell powder (PSP) using a Haake internal mixer at 180 °C and the rotor speed of 50 rpm. Tensile properties of composites were tested using an Instron tensometer. The thermal properties of composites were analyzed using differential scanning calorimetry (DSC). The thermal stability of composites was determined by thermogravimetric analyzer (TGA). The peanut shell powder content was varied from 0 to 40 wt.%. Firstly, a compatibilizer was used to improve the interfacial adhesion of RPP/PSP composites which is polyethylene-co-acrylic acid (PEAA). The tensile strength and elongation at break decreased with increasing peanut shell powder content. The addition of PEAA as a compatibilizer has improved tensile strength, elongation at break and modulus of the composite. Furthermore, the addition of PEAA has slightly enhanced the thermal stability of the composites. During natural weathering for 6 months, it was observed that the incorporation of peanut shell powder has increased the degradability of composites. However, PEAA compatibilized composites showed lower degradability than uncompatibilized composites based on tensile properties, carbonyl indices, crystallinity and weight loss. Secondly, the effect of modification of PSP by using polyvinyl alcohol (PVOH) was examined. It was found that, the tensile properties of modified composites were higher than unmodified composites. The chemical similarity of PSP and PVOH formed ether bonding as shown in IR spectra and such interaction indicated better interfacial adhesion. However, it was observed that, the addition of both PSP and PVOH has boosted up the water absorption percentages due to their hydrophilic nature. The deteriorating impact of composites due to exposure to natural weathering can be seen with the reduction of overall tensile properties. The IR spectra is further confirming the photo-degradation occurred with the appearance of carbonyl (C=O) peaks. Next, the effect of alkaline peroxide pre-treatment was examined. Treated PSP is found to be a promising reinforcement to augment the tensile properties. Subsequently, the tensile properties of composites with treated PSP are somehow slightly retained upon exposure to weathering. However, they are still susceptible to degradation due to the presence of small amounts of monomer and it is verified by FTIR, SEM and weight loss. Lastly, the influences of electron beam (EB) irradiation was evaluated. The gel content increased after the irradiation. However, the increment of gel content was hindered by increasing PSP content. The tensile strength and modulus of the irradiated composites were increased while elongation at break of the irradiated composites decreased. Further analysis on the irradiated composites using FTIR spectra indicated an increase of oxygenated product after irradiation. EB irradiation also enhanced the thermal stability of the composites. After natural weathering, the results agreed that the degradability of irradiated composites was lower than non-irradiated composites.